Sumber Belajar Pendidikan Kewarganegaraan Mengenai Negara Kesatuan Republik Indonesia di Sekolah Dasar - Luh Putu Candri Dewi; I Putu Aris Pramartha; Ni Putu Venny Fatma Dewi; Anak Agung Istri Rahayu Indirayani; I Nengah Suastika (Jurnal Kewarganegaraan, 2022)
AbstrakSalah satu hal terpenting dalam dunia pendidikan adalah tersedianya sumber belajar yang memadai. Sumber belajar adalah suatu acuan atau refrensi yang digunakan dalam suatu pembelajaran guna mempermudah siswa dalam mencapai tujuan pembelajaran atau kompetensi tertentu. Sesuai dengan pembelajaran diterapkan dalam pelajaran PPKn, dimana dalam pelajaran PPKn siswa mempelajari banyak hal yang berkaitan dengan Negara Kesatuan Republik Indonesia. Hal ini sesuai dengan tujuan penelitian ini yaitu (1) Memberbanyak sumber belajar mengenai Negara Kesatuan Republik Indonesia yang di kemas dalam Pembelajaran Pendidikan Kewarganegaarn (PPKn), (2) Mengetahui pengertian dari NKRI, (3) Mengetahui tujuan dari NKRI, (4) Fungsi dari NKRI, dan (5) Upaya menjaga keutuhan NKRI.Kata Kunci: Sumber Belajar, PPKn, NKRIÂ AbstractOne of the most important things in education is the availability of adequate learning resources. Learning resource is a reference or reference used in a lesson to facilitate students in achieving certain learning objectives or competencies. In accordance with the learning applied in Civics lessons, where in Civics lessons students learn many things related to the Unitary State of the Republic of Indonesia. This is in accordance with the objectives of this study, namely (1) to increase learning resources about the Unitary State of the Republic of Indonesia which are packaged in Citizenship Education Learning (PPKn), (2) Knowing the meaning of the Unitary State of the Republic of Indonesia, (3) Knowing the purpose of the Unitary State of the Republic of Indonesia, (4) Functioning from the Unitary State of the Republic of Indonesia, and (5) Efforts to maintain the integrity of the Unitary State of the Republic of Indonesia.Keywords: Learning Resources, PPKn, NKRI